PREVENTION OF THE IMOBILITY CONSEQUENCES IN CRITICALLY ILL PATIENTS - Ana Vanessa Barroso Cerqueira; Eugénia Nunes Grilo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
This article resulted from an intervention project that aimed to prevent the immobility consequences in critically ill patients. The literature review emphasizes that early rehabilitation programs minimize the immobility repercussions with great benefits in people's functionality and quality of life. To study and describe this problem was used the case study methodology. Four hospitalized persons in an intensive care unit participated on an intervention project that included a systematized nursing care in the scope of pressure ulcers prevention and motor and respiratory rehabilitation. The results evaluation allowed to conclude that people who participated in the project maintained or improved the range of motion; did not develop pressure ulcers or respiratory complications. It is concluded that adequate and individualized rehabilitation nursing care planning prevents immobility consequences in critically ill patients.